Tatalaksana ulkus yang disebabkan oleh pecahnya abses peritonsilar Management of ulcer due to rupture of peritonsillar abcess - Astrid Palmasari; Priyo Hadi (Journal of Dentomaxillofacial Science, 2011)
Peritonsillar abcess is a infection of head and neck commonly seen. This infection is caused by infection organismesuch as Streptococcus pyogenes (Group A Beta-Hemolitik streptococcus), Staphylococcus aureus, Haemophilusinfluenzae, Fusobacterium, Prevotella, Porphyromonas, and Peptostreptococcus spp. by the spreading of anaeroborganism to one of loose aerolar space around pharynx and cause the abcess and penentrate to the tonsillar capsulebut which is still in pharynx constrictor muscles boundary. This paper reports a male of 36 years old patient withchief complaint of ulcer on the hard palate accompanied with tonsillar swelling that made difficulty in swallowing.The diagnosis was ulceration due to peritonsillar abcess rupture. Amoxycyllin antibiotic, and benzydamine HClgargle was precribed to cure the ulcers.